Academic Drift in Canadian Institutions of Higher Education: Research Mandates, Strategy, and Culture - Trotter, Lane D.; Mitchell, Amy (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
As with higher-education institutions around the world, British Columbia (BC) and Ontario are increasingly faced with demographic and market pressures that erode the traditional difference between the university and non-university sectors (i.e., colleges and institutes). Key components that ensure these provinces’ institutions preserve their unique roles and differentiations in a changing context, partially driven by their governments, include research mandates, transparency in institutional governance, and strategic documents that resist the academic drift created by institutional isomorphism. Both governments are actively reshaping their post-secondary systems to align with national or regional economic needs, increasing access, streamlining degree completion, and responding to community pressure to have a university or a degree-granting institution. An analysis of the enabling legislation, government policy directives, and institutional documents of both provinces shows that there is a blurring in the distinction between colleges and universities, and the costs associated with this.